ASSOCIATION OF PLASMA HOMOCYSTEINE AND WHITE MATTER HYPODENSITIES IN A SAMPLE OF STROKE PATIENTS - Naveed, Ghazala; Bokhari, Faraz Ahmed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Studies of homocysteine in vascular disorders have yielded conflicting data. There are also differences based on various ethnicities and cultures. In this study, we have examined the homocysteine patterns in local stroke patients, so as to ascertain the homocysteine status in a sample of local population. Homocysteine-white matter hypodensities relationship in stroke is emerging, as an important aspect in stroke pathophysiology and is thought to have prognostic and therapeutic values. Methods: We included 150 stroke patients who were diagnosed as having clinical stroke on the basis of history; physical examination and CT (Computerized Tomography) scan of brain. These patients were recruited from neurology and emergency wards of two public sector hospitals of Lahore. The presence or absence of white matter hypodensities were diagnosed after consultation with a radiologist. Blood samples were collected from the same stroke patients. Results: We found a strong association between white matter hypodensities and total homocysteine in plasma of stroke patients p<0.001. Conclusion: Homocysteine is a risk factor for white matter hypodensities in stroke patients in our study.